1990
DOI: 10.1042/bj2690647
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of the interaction of prolactin with its receptor in the rabbit mammary-gland microsomes

Abstract: The interaction of prolactin (PRL) with its membrane receptor depends markedly on temperature. Thermodynamic parameters for this reaction have been-evaluated from data for time-course kinetics and equilibrium binding at multiple temperatures between 19 and 31 'C. The free-energy change with temperature and the van't Hoff plot were found to be linear. These suggest that there are minimal structure changes at the PRL-receptor contact site over this temperature range. The positive signs of the entropy and enthalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Van't Hoff plot demonstrated linear regression (R 2 =0.982) as the enthalpy change (ΔH) is constant throughout the test conducted at temperature range of 298-323 K. Additionally, linear plot suggested that the structure of binding site of carrageenans does not have significant change in that temperature range tested [19]. Negative value of ΔH (-18.54 kJ mol -1 ) described that the MB-Iota-carrageenan complexation is an exothermic process.…”
Section: Van't Hoff Equation For Thermodynamic Studymentioning
confidence: 97%
“…Van't Hoff plot demonstrated linear regression (R 2 =0.982) as the enthalpy change (ΔH) is constant throughout the test conducted at temperature range of 298-323 K. Additionally, linear plot suggested that the structure of binding site of carrageenans does not have significant change in that temperature range tested [19]. Negative value of ΔH (-18.54 kJ mol -1 ) described that the MB-Iota-carrageenan complexation is an exothermic process.…”
Section: Van't Hoff Equation For Thermodynamic Studymentioning
confidence: 97%
“…Microsomes were prepared from mid-lactating rabbit mammary glands. The protocol for the PRL-binding assay has been described previously (Sakai et al, 1990). In the present investigation the concentrations of microsomes and 1251.…”
Section: Association and Dissociation Proceduresmentioning
confidence: 99%
“…where R and Tare the gas constant and the absolute temperature respectively. The free energy of activation (AG:), enthalpy of activation (AHP) and entropy of activation (AST) for dissociation were calculated according to transition state theory (Sakai et al, 1990). All thermodynamic data were standardized at 25 'C.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 2 more Smart Citations